SOME FACTORS AFFECTING TAX AVOIDANCE - Tan, Richard Bryan; Hastuti, Rini Tri (Graduate Program of Universitas Tarumanagara, 2024)
Companies in Indonesia have indications of committing tax avoidance as seen from the existence of a tax amnesty policy that took effect from 1 July 2016 to 31 March 2017. Tax evasion by companies shows that the mechanism of corporate governance is not working effectively and efficiently. It was indicated that these companies did not apply the principles of Good Corporate Governance. This study aims to obtain evidence of institutional ownership, audit committees, company size and sales growth on tax avoidance in financial sector companies listed on the IDX in the 2019-2021 period. This study uses independent variables, namely institutional ownership, audit committee, company size and sales growth and the dependent variable, namely tax evasion. The method used in this research is purposive sampling. The number of samples obtained by this method is 174 samples. The results of this model estimation test show the use of the Random Effect Model (REM) as a model for regression analysis. The results of the regression analysis with the REM model show that institutional ownership, firm size, and sales volume do not have a significant effect on tax evasion. The audit committee has results that affect tax evasion.